Phase-controlled synthesis of monolayer ternary telluride with a random local displacement of tellurium atoms - Tang, Bijun (2021)
Alloying 2D transition metal dichalcogenides has opened up new opportunities for bandgap engineering and phase control. Developing a simple and scalable synthetic route is therefore essential to explore the full potential of these alloys with tunable optical and electrical properties. Here, the direct synthesis of monolayer WTe2xS2(1−x) alloys via one-step chemical vapor deposition (CVD) is demonstrated. The WTe2xS2(1−x) alloys exhibit two distinct phases (1H semiconducting and 1T ′ metallic) under different chemical compositions, which can be controlled by the ratio of chalcogen precursors as well as the H2 flow rate. Atomic-resolution scanning transmission electron microscopy–annular dark field (STEM-ADF) imaging reveals the atomic structure of as-formed 1H and 1T ′ alloys. Unlike the commonly observed displacement of metal atoms in the 1T ′ phase, local displacement of Te atoms from original 1H lattice sites is discovered by combined STEM-ADF imaging and ab initio molecular dynamics calculations. The structure distortion provides new insights into the structure formation of alloys. This generic synthetic approach is also demonstrated for other telluride-based ternary monolayers such as WTe2xSe2(1−x) single crystals.